Effects Of Probiotic, Lactobacillus Acidophilus On Pathogenic Bacteria, Growth, Hematological Parameters And Histopathology Of African Catfish (Clarias Gariepinus) - Al-Dohail , Mohammed Abdullah Salem (2010)

(untitled)
Four experiments were carried out to evaluate the in vitro and in vivo used of Lactobacillus acidophilus as a biocontrol agent against some common fish pathogenic bacteria (Staphylococcus xylosus, Aeromonas hydrophila gr.2 and Streptococcus agalactiae) and its effects on growth performance, hematological parameters, and histopathology of African catfish, Clarias gariepinus. In the first experiment, the antimicrobial activity of L. acidophilus against common fish pathogenic bacteria was studied in vitro. In the second experiment, 2 experimental diets were formulated comprising of a control (non-probiotic diet) and a L. acidophilus supplemented at a concentration of 3.01 x107 colonies per gram of diet (probiotic diet).